Cost-Effectiveness Analysis of Pan-Genotypic Sofosbuvir-Based Regimens for Treatment of Chronic Hepatitis C Genotype 1 Infection in China - Zhou, Hui Jun; Cao, Jing; Shi, Hui; Naidoo, Nasheen; Semba, Sherehe; Wang, Pei; Fan, Yi Fan; Zhu, Shui Cheng (Frontiers in Public Health, 2021)
Background Hepatitis C virus (HCV) genotype 1 is the most prevalent HCV infection in China. Sofosbuvir-based direct antiviral agent (DAA) regimens are the current mainstays of treatment. Sofosbuvir/velpatasvir (SOF/VEL) and sofosbuvir/ledipasvir (SOF/LDV) became reimbursable in China in 2020. Thus, this study aimed to identify the optimal SOF-based regimen and to inform efficient use of healthcare resources by optimizing DAA use in treating HCV. Methods and Materials A modelling-based cost-utility analysis was conducted from the payer’s perspective targeting adult Chinese patients with chronic HCV genotype 1 infection. Direct medical costs and health utilities were inputted into a Markov model to simulate lifetime experiences of chronic HCV infected patients after receiving SOF/LDV, SOF/VEL or the traditional strategy of pegylated interferon (pegIFN) + ribavirin (RBV). Discounted lifetime cost and quality adjusted life years (QALYs) were computed and compared to generate the incremental cost utility ratio (ICUR). An ICUR below the threshold of 31,500 $/QALY suggested cost-effectiveness. Deterministic and probabilistic sensitivity analyses were performed to examine the robustness of model findings. Results Both SOF/LDV and SOF/VEL regimens were dominant to pegIFN + RBV by creating more QALYs and incurring less cost. SOF/LDV produced 0.542 more QALY but cost $10,390 less than pegIFN + RBV. Relative to SOF/LDV, SOF/VEL had an ICUR of 168,239 $/QALY which did not meet the cost-effectiveness standard. Therefore SOF/LDV was the optimal strategy. These findings were robust to linear and random variations of model parameters. However, reducing the SOF/VEL price by 40% would make this regimen the most cost-effective option. Conclusions SOF/LDV was found to be the most cost-effective treatment, and SOF/VEL also economically dominant to pegIFN + RBV. These findings indicated that replacing pegIFN + RBV with DAA regimens could be a promising strategy.